2014
DOI: 10.1038/npp.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

FKBP5 Moderates Alcohol Withdrawal Severity: Human Genetic Association and Functional Validation in Knockout Mice

Abstract: Alcohol withdrawal is associated with hypothalamic-pituitary-adrenal (HPA) axis dysfunction. The FKBP5 gene codes for a cochaperone, FK506-binding protein 5, that exerts negative feedback on HPA axis function. This study aimed to examine the effects of single-nucleotide polymorphisms (SNPs) of the FKBP5 gene in humans and the effect of Fkbp5 gene deletion in mice on alcohol withdrawal severity. We genotyped six FKBP5 SNPs (rs3800373, rs9296158, rs3777747, rs9380524, rs1360780, and rs9470080) in 399 alcohol-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…Our proof of principle approach combines both mouse and human data to systematically evaluate and nominate specific PPARs. An overall similar approach recently showed that SNPs of FKBP5 were associated with alcohol withdrawal in humans, and Fkbp5 knockout mice also showed greater withdrawal severity (Huang et al, 2014). Our results provide support for the first human genetic link between PPARs and alcohol-related phenotypes and suggest that further studies are warranted to evaluate repurposing PPAR agonists for treating AD.…”
Section: Discussionmentioning
confidence: 95%
“…Our proof of principle approach combines both mouse and human data to systematically evaluate and nominate specific PPARs. An overall similar approach recently showed that SNPs of FKBP5 were associated with alcohol withdrawal in humans, and Fkbp5 knockout mice also showed greater withdrawal severity (Huang et al, 2014). Our results provide support for the first human genetic link between PPARs and alcohol-related phenotypes and suggest that further studies are warranted to evaluate repurposing PPAR agonists for treating AD.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have implicated FKBP5 sequence and expression variation in moderating responses to alcohol use. For example, a recent study by Huang and associates demonstrated that FKBP5 genetic variation moderated the severity of alcohol withdrawal in both humans and rodents (Huang et al, 2014). Using a genome wide approach, Bell and associates showed that acute alcohol intake in rats was associated with increased transcription of FKPB5 (Bell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, for the design and interpretation of DAE analyses, there is high LD across FKBP5 including between rs1360780 (A/G) and rs3800373 (G/T) (Bevilacqua et al , 2012, Binder et al , 2004, Huang et al , 2014, Roy et al , 2010). This haplotype has been associated with differential induction of FKBP5 mRNA and protein by GR activation (Binder et al , 2004) and with GR resistance such that A allele carriers of healthy controls have a prolonged cortisol response even to minor stressors (Ising et al , 2008).…”
Section: Discussionmentioning
confidence: 99%